Effect of Silane on Shear Bond Strength of Two Porcelain Repair Systems - Ahmadzadeh, Asadollah; Ghasemi, Zahra; Panahandeh, Narges; Golmohammadi, Farnoosh; Kavyani, Azita (Journal of Dental School, 2019)
Objectives: Ceramics have advantages such as optimal esthetics and biocompatibility. However, in the oral environment, they are subjected to high levels of stress due to masticatory forces, saliva, thermal changes and alterations of pH, which increase their risk of fracture. Since replacement of these restorations is costly and time-consuming, composite resin is often used for intraoral repair of these restorations. This study aimed to assess the shear bond strength of two porcelain repair systems by Pulpdent and Ultradent and evaluate the effect of number of silane layers on the shear bond strength. Methods: This invitro experimental study was conducted on 66 porcelain blocks measuring 3×5×8mm. In each kit, samples were randomly divided into three groups of 11. Silane was not used for group one. Groups two and three received one coat and two coats of silane, respectively. After surface preparation, composite was bonded to ceramic surfaces. Data were analyzed using two-way ANOVA. Results: The LSD test showed that application of Ultradent silane significantly affected the shear bond strength (P<0.05) while Pulpdent silane had no such effect (P=0.89). Application of one layer and two layers of silane was not significantly different (P=0.94). Conclusion: Ultradent ceramic repair kit yields higher shear bond strength at the ceramic-composite interface compared to Pulp dent ceramic repair kit. Use of one or two layers of silane does not make any significant difference with regard to the shear bond strength of ceramic to composite.